Poola-Ukraina kodusõda Ida-Galiitsias: ajalugu ja mälestamine [The Polish-Ukrainian Civil War in East Galicia: History and Remembrance] - Mick, Christoph (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2015)
The Polish-Ukrainian war 1918/19 is the key to understanding the conflicts in Lviv and eastern Galicia in the inter-war period. The war brought developments to a temporary halt, and created new conditions which particularly affected the way conflicts were waged. Certain historical options, such as those aimed at an equitable settlement, were rendered improbable while others (such as a violent solution to the conflict) became more likely.For the Jewish population, November 1918 was inextricably linked to the memory of the pogrom. It was therefore difficult for East Galician Jews to participate in Polish celebrations.The Ukrainians consciously formed their own community of memory. The experiences of November 1918 were handed down to subsequent Polish and Ukrainian generations through the practice of remembrance and commemoration in Polishand Ukrainian society. The younger generation of Ukrainian nationalists rejected the democratic concepts of the older generation of politicians and drew their own lessons from the experiences of the Polish-Ukrainian war. The mutual experiences of violence were an integral part of the mental baggage of the Lviv Poles, Ukrainians and Jews when World War II erupted.